THE UNIQUE Y-ZIRCON FROM THE ICHET′YU POLYMINERAL OCCURRENCE (CENTRAL TIMAN) - A.B. Makeev; S.E. Borisovsky; O.M. Zhilicheva; T.B. Bayanova; S.G. Skublov (Минералогия, 2015)
The morphology, composition, color CL, age, and the source of zircon of the Ichet′yu occurrence are studied. The U-Pb age of zircons from the occurrence widely varies from 2247 and 1478 Ma with a difference of 700 Ma within the Paleo-Mezoproterozoic. The Paleoproterozoic zircons are heavily rounded and often isometric and are characterized by weak internal zoning. The color grains of these zircons are mat white and brown. The Mezoproterozoic zircons are characterized by short prismatic habit and clear thin rhythmic internal zoning. Their color is light yellow and, dominantly, light pink. The morphological features of zircons, namely, the average roundness and good preservation allow us to suggest the proximal source of their runoff. It is concluded that the basement of the Central Timan (the most likely source of zircon of the Ichet′yu occurrence) is composed of the Paleo-Mezoproterozoic continental igneous rocks and is probably a continuation of the Arkhangelsk AR-PR mobile belt.